Penguatan Manajeman Keuangan di Madrasah Ibtidaiyah Nahdlatut Mubtadiin Nangger Sampang Mashuri - Mashuri , Mashuri (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2022)
Finance is one of the resources that directly supports the effectiveness and efficiency of education management. In the implementation of financial education, it has a very determining potential and is an inseparable part in the study of educational management. This study is intended to answer the problems: (1) How is financial planning in Nahdlatut Mubtadiin Nangger Sampang. (2) How is the financial implementation of MI Al Khoiriyyah 1 Semarang. (3) How is the financial evaluation of MI Al Khoiriyyah 1 Semarang. This research is a type of qualitative research, which was carried out at Nahdlatut Mubtadiin Nangger Sampang. The data was obtained by means of interviews, observation and documentation. All data was analyzed using a descriptive approach using the logic of induction, deduction and reflection. This study shows the results that: (1) Nahdlatut Mubtadiin Nangger Sampang in carrying out planning, namely in the form of budget preparation, has done it well. (2) In financial implementation, Nahdlatut Mubtadiin Nangger Sampang does this by bookkeeping of incoming and outgoing funds. (3) The evaluation carried out by Nahdlatut Mubtadiin Nangger Sampang takes the form of supervision and inspection. Supervision is carried out by the madrasa head as a leader who is directly responsible to any party. Meanwhile, the inspection is carried out by the head of the madrasah and the madrasah committee. Inspections are carried out on the budget prepared, cash, namely through incoming and outgoing funds and on goods owned by the madrasah. The transparency built by Nahdlatut Mubtadiin Nangger Sampang is carried out by providing notifications to students' parents through notification letters, as well as accountability to them by providing information about the use of funds if necessary.